Model Problem Based Learning dalam Pembelajaran IPA pada Materi Peredaran Darah: Sebuah Studi Eksperiemen di Sekolah Dasar - Jihan Syafira Rustanto; Achmad Fanani; Danang Prasetyo (Journal of Edukasi Borneo, 2020)
The purpose of this study was to find out: (1) the effect of the problem based learning (PBL) model on learning outcomes on the subject of circulatory for fifth grade elementary school (SD) students in Surabaya; (2) Student activity in applying the PBL model on learning outcomes on the subject of circulatory for fifth grade elementary school (SD) students in Surabaya. This study was a quasi experimental design type of posttest-only control design (nonequivalent control group design). The population of this study were students of class V SD in Surabaya, using the cluster sampling technique (area sampling), the sample class V A was selected as the control class and class V B as the experimental class. Data collection techniques used tests as the main data supported by student observation sheets. The data analysis technique used parametric inferential statistics with the help of SPSS version 16.0 software. These results were: (1) the implementation of PBL models in the activities of fifth grade elementary school students is categorized as very good. (2) Sig. (2-tailed) 0.000 <0.05, thus Ho is rejected and H1 is accepted, the research could be stated that there was an effect of the PBL model on learning outcomes on the subject of circulatory for grade V of SD students. ABSTRAK Tujuan penelitian ini adalah untuk mengetahui: (1) Pengaruh model problem based learning (PBL) terhadap hasil belajar materi peredaran darah pada siswa kelas V Sekolah Dasar (SD) di Surabaya; (2) Aktivitas siswa dalam penerapan model PBL pada pembelajaran IPA materi peredaran darah siswa kelas V SD. Penelitian ini merupakan penelitian quasi experimental design tipe posttest-only control design (nonequivalent control group design). Populasi penelitian ini adalah siswa kelas V SD di Surabaya, dengan mengunakan teknik Cluster sampling (area sampling) terpilih sampel kelas V A sebagai kelas kontrol dan kelas V B sebagai kelas eksperimen. Teknik pengumpulan data menggunakan tes sebagai data utama dengan didukung lembar observasi peserta didik. Teknik analisis data menggunakan statistic inferensial parametrik dengan berbantuan software SPSS versi 16.0. Hasil ini dibuktikan dengan: (1) Pelaksanaan model pembelajaran PBL pada aktivitas siswa kelas V SD dikategorikan sangat baik. (2) Sig. (2-tailed) 0,000 < 0,05 dengan demikian Ho ditolak dan H1 diterima, penelitian dapat dinyatakan ada pengaruh model PBL learning terhadap hasil belajar materi peredaran darah pada siswa kelas V SD. KATA KUNCI: Problem Based Learning, Hasil Belajar, Aktivitas Siswa.